Brooding behavior of chickens with reference to a genetic perspective: Perilaku Mengeram pada Ayam Ditinjau dari Perspektif Genetika - Bilyaro, Woki; Widyasari, Dhini Nova; Azis, Arif Rahman; Dani, Muhammad (Buletin Peternakan Tropis, 2025)
Brooding behavior in chickens is a natural trait that is essential for the continuation of the species. While this behavior is advantageous for hatching eggs, it can also be a drawback for farmers focused on eggs production. Prolonged brooding behavior has the tendency to delay hens from reaching the following egg-laying period. The purpose of this study is to investigate how brooding behavior in chickens is from a genetic perspective. The elimination of the brooding trait can be achieved by improving genetic quality through selection methods such as those used in laying breeds. Once the brooding trait can be reduced or eliminated through selection, the production of eggs will be increased. Prolactin plays a role in the behavior of the hen in terms of incubation, feeding, and nest guarding behavior. Focused selection in chicken breeding has provided farmers with the opportunity to improve brooding traits based on specific objectives, as well as to produce chickens that are better at egg production or for chickens that are more suitable for breeding. Understanding these genetic mechanisms allows farmers to perform genetic selection based on the security of prolactin genes and their associations to control the brooding behavior in accordance with the breeding objectives, either to increase egg production or to maintain natural traits in local chickens. The conclusion is that brooding traits in chickens are highly influenced by various factors, including genetic, hormonal and environmental factors